Utopian Visions - ROSENBERG, VIVIAN (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course explores utopian visions of writers and filmmakers; their criticisms of their own societies; and their fears and dreams about the future. All ideas, of course, are rooted in and constructed in response to particular cultural environments . Thus, we will study the literature of utopias within the context of changing world-views, changing notions of the individual, the family, and the community, and changing hopes and expectations. The purpose of the course is to help us understand the problems and possibilities of our own times by examining how serious and concerned thinkers reacted to an imperfect world.